2020
DOI: 10.1152/ajpregu.00257.2019
|View full text |Cite|
|
Sign up to set email alerts
|

Role of the carotid chemoreceptors in insulin-mediated sympathoexcitation in humans

Abstract: Objective: Given recent evidence from rodents supporting a novel role for the carotid bodies in insulin‐mediated sympathoexcitation, we sought to determine whether carotid chemoreceptor desensitization would reduce muscle sympathetic nerve activity (MSNA) during hyperinsulinemia in humans. Methods: Young, healthy subjects (n=4, 30±2 yrs) breathed hyperoxic gas (End‐tidal O2 = 100%, PaO2 505±13 mmHg) for 15 min at baseline and during steady‐state hyperinsulinemia (5±1 vs 53±1 µU/mL). Hyperinsulinemia was achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
0
8
1
Order By: Relevance
“…If at a first sight these results seem conflicting with our hypothesis that increased CB chemosensitivity promotes glucose homeostasis disruption due to the overactivation of the sympathetic nerve system, they are not, as we previously concluded that reductions in CB chemoreceptor activity positively affects insulin signaling pathways in visceral adipose tissue and liver, but not in skeletal muscle (9). Indeed, the study of Limberg et al (39) corroborate our own since we also did not observe changes in glucose uptake in muscle after CSN ablations (9).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…If at a first sight these results seem conflicting with our hypothesis that increased CB chemosensitivity promotes glucose homeostasis disruption due to the overactivation of the sympathetic nerve system, they are not, as we previously concluded that reductions in CB chemoreceptor activity positively affects insulin signaling pathways in visceral adipose tissue and liver, but not in skeletal muscle (9). Indeed, the study of Limberg et al (39) corroborate our own since we also did not observe changes in glucose uptake in muscle after CSN ablations (9).…”
Section: Discussioncontrasting
confidence: 64%
“…In agreement also with our findings, that CB chemosensitivity correlates with fasting plasma insulin levels, is the work by Barbosa et al (38) where they show in humans that elevated plasma insulin increases minute ventilation independently of changes in glucose. More recently, the same authors examined the contribution of the CB chemoreceptors to the insulin-mediated increases in muscle sympathetic nerve activity (MSNA) in healthy humans and found that the attenuation of CB activity by low-dose dopamine or by hyperoxia, did not altered insulin-mediated increase MSNA burst frequency, suggesting that CB withdrawal in young, healthy men and women did not attenuate the sympathoexcitatory response to hyperinsulinemia (39). If at a first sight these results seem conflicting with our hypothesis that increased CB chemosensitivity promotes glucose homeostasis disruption due to the overactivation of the sympathetic nerve system, they are not, as we previously concluded that reductions in CB chemoreceptor activity positively affects insulin signaling pathways in visceral adipose tissue and liver, but not in skeletal muscle (9).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in [Ca 2+ ] i in rat type I cells in response to hypoxia can be attenuated by D 2 -receptor agonists [ 67 ]. D 2 -receptors have now also been positively confirmed in the human CB [ 68 ] and DA infusion to depress CB function is commonly used to estimate CB contribution to pathophysiological reflexes in humans [ 69 , 70 , 71 ]. Whether or not DA completely silences the CB chemoafferent discharge in humans is unknown.…”
Section: G αS and G αI Protementioning
confidence: 99%
“…These experiments provide strong support for a physiological role of the carotid bodies in glucose homeostasis and suggest that circulating insulin can activate the carotid bodies. In humans, the physiological role of insulin on carotid body function still needs to be clarified, Infusions of insulin have been shown to increase muscle sympathetic nerve activity, but this could not be attenuated by low dose dopamine and/or hyperoxia suggesting acute insulin infusion does not affect carotid body function ( Limberg et al, 2020 ). However, in chronic conditions like diabetes, insulin may well have an important role in glucose homeostasis mediated by the carotid bodies ( Vera-Cruz et al, 2015 ).…”
Section: What Are the Potential Transmitters That Can Regulate Carotimentioning
confidence: 99%